2014
DOI: 10.1155/2014/430164
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Optimal Parameters in Hydrothermal Method for the Synthesis of ZnO Nanorods

Abstract: We investigated a two-step method to deposit the ZnO-based nanostructure films, including nanorods and nanoflowers. In the first step, sputtering method was used to deposit the ZnO films on SiO2/Si substrates as the seed layer. In the second step, Zn(NO3)2–6H2O and C6H12N4were used as precursors and hydrothermal process was used as the method to synthesize the ZnO films. After that, the ZnO films were measured by an X-ray diffraction pattern and a FESEM to analyze their crystallization and morphology. We had f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The photoluminescence (PL) spectrum of the ZnO exhibits two excitonic peaks [6], one in the UV region and other at visible region [7,8]. The broad emission band in the visible region (420 nme750 nm) is attributed to deep level defects in ZnO [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The photoluminescence (PL) spectrum of the ZnO exhibits two excitonic peaks [6], one in the UV region and other at visible region [7,8]. The broad emission band in the visible region (420 nme750 nm) is attributed to deep level defects in ZnO [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The Eu 3+ -doped and In 3+ -doped ZnO nanowires were synthesized at temperatures of 100 to 60 • C for 1 h using a hydrothermal method. Previously, we used a well-designed structure to grow ZnO-based nanostructured materials via a hydrothermal method [19]. We found that when Zn(NO 3 ) 2 -6H 2 O and C 6 H 12 N 4 were used as reagents to synthesize ZnO-based nanostructured materials, the concentration of the diluted solution had important effects on the synthesis results.…”
Section: Methodsmentioning
confidence: 99%
“…We found that when Zn(NO 3 ) 2 -6H 2 O and C 6 H 12 N 4 were used as reagents to synthesize ZnO-based nanostructured materials, the concentration of the diluted solution had important effects on the synthesis results. We, therefore, fixed the concentration of the diluted solution as a reference point [19].…”
Section: Methodsmentioning
confidence: 99%
“…The hydrothermal method is a low-temperature process to synthesize ZnO nanomaterials with different structures. For example, Chen et al found that as SiO 2 /Si substrates faced different directions or ZnO-based materials grew at different times, ZnO nanomaterials had different structures, including chrysanthemum flower-like clusters, nonuniform nanorods with different lengths and diameters, large hexagonal bars, and nanoflowers . When the hydrothermal method is used to synthesize ZnO nanomaterials, the synthesis parameters, including the solution concentration, solution type, synthesis temperature, and synthesis time, will affect their outward appearance and morphology. However, as the synthesis parameters are well controlled, uniformed ZnO nanorods can successfully grow perpendicular to the substrate in a large area …”
Section: Introductionmentioning
confidence: 99%